The information practices of software professionals in their cultural contexts: a phenomenological and hermeneutic approach - Pinheiro de Souza, Leonardo Pereira [UNESP]; Bassan de Moraes, Cassia Regina [UNESP]; Pomim Valentim, Marta Ligia [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2020)
It is verified that software developers use information and knowledge for programming and modification of program's source codes. It is understood that the collective ways of dealing with information, informational culture, are intertwined in organizational culture. It is evident that organizational cultures are peculiar to each company but influenced by shared perspectives in a professional culture. It is noted that informational practices, an emerging theme in user studies, show subjective and collective factors in the subjects' relationship with information and knowledge. It is aimed, therefore, to investigate the informational practices of software developers at the intersection of professional, organizational and informational cultures, verifying collective informational values, implicit in individual discourses. It is intended to identify informational values common among software companies, representing professional culture, and values peculiar to organizational cultures. It also aimed to identify positive and factors to improve in informational practices. Multiple case studies are used as methodological procedures, through interviews with managers and programmers from two companies. The categorical content analysis and Paul Ricoeur's hermeneutic phenomenology is used to analyze and interpret data, elucidating collective aspects underlying individual discourses. The results show that common cultural elements in organizations emphasize informal socialization of information and knowledge, with difficulties in documenting them, primacy of the Internet as an informational source, and other aspects. It is concluded that informational practices arise at the confluence of multiple cultural factors with professional practice and that, being built on work's empirical experience, they need to be reflected through contributions from Information Science, correcting gaps and improving them, to achieve organizational objectives.
Keywords: User studies; Phenomenology; Hermeneutics; Programming; Organizational culture